Stent-assisted coil embolization of ruptured vertebral artery dissected aneurysm with severe stenosis of bilateral vertebral artery V4 segment by the transmountain technique: a case report and review of the literatures - Hao, Guangzhi; Zhang, Zijun; Han, Yuwei; Huan, Yu; Dong, Yushu; Zhao, Haiyang; Liang, Guobiao (Frontiers in Surgery, 2025)
A 46-year-old woman presented with acute head and neck pain for 10 h. Head CT showed subarachnoid hemorrhage (SAH) and digital subtraction angiography (DSA) identified a ruptured dissected aneurysm of the right vertebral artery with severe artery stenosis. Moreover, an unruptured dissecting aneurysm and severe vascular stenosis were also found in the left vertebral artery. How to deal with ruptured bleeding aneurysm and prophylactically deal with contralateral unruptured dissecting aneurysm and the stenosis of the vertebral artery has become a thorny problem. By adopting the Transmountain technique, we used a single Enterprise-2 stent to cover the neck of the right ruptured vertebral artery dissection aneurysm and the severe stenosis of the distal vessel, while bypassing the vertebrobasilar artery junction to continue covering the severe stenosis and the unruptured dilated dissection of the contralateral vertebral artery. This new stent-assisted approach may provide a reference for clinicians in the treatment of complex dissection aneurysms.